Pyonephrosis Presenting as Lumbar Abscess-An Uncommon Clinicoradiological Entity - Rajul Rastogi; Neha; Vijai Pratap; Gulzari Lal Meena (Archives of Clinical Nephrology - Peertechz Publications, 2020)
Pyonephrosis secondary to an obstructing calculus in renal pelvis, pelviureteric junction or ureter usually presents clinically with fever, loin pain and other signs of urinary tract infection. Rarely, severe thinning of renal parenchyma in pyonephrosis may allow direct forniceal rupture into the retroperitoneum producing retroperitoneal abscess that might be the only presenting complaint without any complaints related to renal system. Prompt and aggressive management including optimal imaging and correct diagnosis is needed in such cases to prevent further complication. Hence, this article focuses on the rare spontaneous rupture of calculus pyonephrosis in to ipsilateral psoas & quadratus lumborum muscle to clinically present as a lumbar pain & abscess, presentation not described before in medical literature.